2022
DOI: 10.3390/foods11050724
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, Techno-Functional and Structural Properties of Black Soldier Fly (Hermetia illucens) Larvae Flours and Protein Concentrates

Abstract: Due to their protein content and balanced amino acid profile, edible insects have been described as an excellent alternative protein source to combat malnutrition. As the global population continues to grow, edible insects such as the black soldier fly larvae (BSFL) may contribute to food security. The effect of different protein extraction methods, i.e., alkaline solution and acid precipitation (BSFL-PC1) and extraction with an alkali (BSFL-PC2), on the nutritional, techno-functional, and structural propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 47 publications
4
5
1
Order By: Relevance
“…In this study, insect protein hydrolysates showed OHC values ranging between 3.54 and 4.83 g/g, which was within the previously reported range, including BSF (0.8–5.2 g/g) [ 35 , 36 , 37 ] and cricket (1.42–3.5 g/g) [ 38 , 39 , 40 ]. Crickets had the highest OHC compared to the other sources, and the mussels and oysters were revealed to have the lowest OHC among the selected protein sources ( p < 0.05), which could be due to the higher content of hydrophobic amino acids in oyster, mussel, and lugworm hydrolysates compared to those of BSF and cricket hydrolysates.…”
Section: Resultssupporting
confidence: 90%
“…In this study, insect protein hydrolysates showed OHC values ranging between 3.54 and 4.83 g/g, which was within the previously reported range, including BSF (0.8–5.2 g/g) [ 35 , 36 , 37 ] and cricket (1.42–3.5 g/g) [ 38 , 39 , 40 ]. Crickets had the highest OHC compared to the other sources, and the mussels and oysters were revealed to have the lowest OHC among the selected protein sources ( p < 0.05), which could be due to the higher content of hydrophobic amino acids in oyster, mussel, and lugworm hydrolysates compared to those of BSF and cricket hydrolysates.…”
Section: Resultssupporting
confidence: 90%
“…05 ). Insect hydrolysates’ emulsion capacity was in the range of 57.8-60%, which is in agreement with other researchers finding (39-98%) (Adebowalea et al, 2005; Mshayisa et al, 2022; Trinh & Supawong, 2021). The emulsion capacity of bivalve mollusks fell consistently in the 35-65% range as found by other studies (Haldar et al, 2018; Naik et al, 2020).…”
Section: Resultssupporting
confidence: 92%
“…In this study, insect protein hydrolysates showed OHC values ranging between 3.54 to 4.83 g/g, which was within the previously reported range, including BSF (0.8-5.2 g/g) (Mshayisa et al, 2022;Purschke et al, 2018;Wang et al, 2021) and cricket (1.42-3.5 g/g) (Leni et al, 2020;Stone et al, 2019;Zielińska et al, 2018). Cricket had the highest OHC compared to other sources, and the mussels and oysters revealed the lowest OHC among the selected protein sources (P < 0.05), which could be due to the higher content of hydrophobic amino acids in oyster, mussels and lugworm hydrolysates compared to BSF and cricket hydrolysates.…”
Section: Dh and Techno-functional Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…Investigating the nutritional, techno-functional and structural properties of Black Soldier Fly ( Hermetia illucens ) larval flours (BSFL) and protein concentrates has been the subject of the paper by Mshayisa et al [ 17 ]. The highest protein content (73.35%) was obtained under alkaline and acid precipitation extraction (BSFL-PC1).…”
mentioning
confidence: 99%